2021
DOI: 10.3390/pharmaceutics13070944
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Rotator Cuff Healing with Farnesol-Impregnated Gellan Gum/Hyaluronic Acid Hydrogel Membranes in a Rabbit Model

Abstract: Most rotator cuff (RC) tears occur at the bone–tendon interface and cause disability and pain. Farnesol, a sesquiterpene compound, can exert antioxidative and anti-inflammatory effects and promote collagen synthesis. In this rabbit model, either commercial SurgiWrap membrane or hydrogel membranes containing various compositions of gellan gum, hyaluronic acid, and farnesol (hereafter GHF membranes) were applied to the tear site, and the repair of the cuff was examined 2 and 3 weeks afterward. The designed membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…13 During rotator cuff healing after rotator cuff repair, inflammatory cells accumulate and result in fibrotic tissue formation, which impairs tendon healing instead of regenerating the tendon itself. 13,28,34 HA possesses anti-inflammatory properties; thus, it promotes tendon-to-bone healing. 8 Moreover, HA binds and interacts with specific cell-associated receptors, such as CD44.…”
Section: Discussionmentioning
confidence: 99%
“…13 During rotator cuff healing after rotator cuff repair, inflammatory cells accumulate and result in fibrotic tissue formation, which impairs tendon healing instead of regenerating the tendon itself. 13,28,34 HA possesses anti-inflammatory properties; thus, it promotes tendon-to-bone healing. 8 Moreover, HA binds and interacts with specific cell-associated receptors, such as CD44.…”
Section: Discussionmentioning
confidence: 99%
“…The membranes could swell rapidly and adhere to the tear site, acting as a barrier and farnesol source during the repair period. Results indicated that farnesol enhanced collagen production and the hydrogel membranes was promising in the repair of rotator cuff injuries ( Lin et al, 2021 ).…”
Section: The Functions Of Hydrogel Used In Rotator Cuff Repairmentioning
confidence: 99%
“…(B) In vivo application and evaluation of Cur&Mg-QCS/PF hydrogels. (Reprinted from ( Lin et al, 2021 ) with permission from Theranostics).…”
Section: The Functions Of Hydrogel Used In Rotator Cuff Repairmentioning
confidence: 99%
“… 19 Farnesol can modulate connective tissue and ECM synthesis, which is required for wound healing 20 and rotator cuff repair. 21 Cartilage reconstruction is challenging because cartilage has poor intrinsic defect-repairing abilities. Studies have identified that in chondrocytes, phenotypic instability occurs with changes in the cell volume and morphology before considerable cartilage degeneration and loss, which might be essential for indicating the early stages of cartilage loss.…”
Section: Introductionmentioning
confidence: 99%